The Impact of a 10-Month Synbiotic Intake on eGFR, Uremic Toxins, Oxidative Stress, and Inflammatory Markers in Non-Dialysis Chronic Kidney Disease Patients: A Prospective, Non-Randomized, Placebo-Controlled Study - Teodor Kuskunov; Eduard Tilkiyan; Irina Zdravkova; Siyana Valova; Krasimir Boyanov; Anelia Bivolarska (Medicina, 2025)
Background and Objectives: The worldwide prevalence of chronic kidney disease (CKD) continues to increase, representing a major concern for public health systems. CKD is associated with gut microbiota dysbiosis, which may exacerbate disease progression by increasing the levels of uremic toxins, systemic inflammation, and oxidative stress. Modulation of the gut microbiota through biotic supplementation has been proposed as a potential therapeutic strategy to slow CKD progression and mitigate its complications. This study aimed to evaluate the effect of 10-month synbiotic supplementation on estimated glomerular filtration rate (eGFR), circulating concentrations of indoxyl sulfate (IS), p-cresyl sulfate (p-CS), interleukin-6 (IL-6), and malondialdehyde (MDA) in patients with stage IV–V CKD not receiving dialysis, in comparison to placebo. Materials and Methods: Fifty non-dialysis CKD IV–V patients were assigned (n = 25 each) via matched, non-randomized allocation (age, sex, and primary disease) to synbiotic or placebo. This single-blind, placebo-controlled trial blinded participants and laboratory personnel. The synbiotic group received daily capsules containing Lactobacillus acidophilus La-14 (2 × 1011 CFU/g) + fructooligosaccharides; controls received identical placebo. Adherence was monitored monthly (pill counts, diaries), with < 80% over two visits resulting in withdrawal. The eGFR, IS, p-CS, IL-6, and MDA were measured at baseline and month 10. Results: Forty-two patients (21/arm) completed the study; eight withdrew (4 per arm). At 10 months, the change in eGFR was −1.2 ± 2.5 mL/min/1.73 m2 (synbiotic) vs. −3.5 ± 3.0 mL/min/1.73 m2 (placebo); between-group difference in change was 2.3 mL/min/1.73 m2 (95% CI: 0.5–4.1; p = 0.014; adjusted p = 0.07). IS decreased by −15.4 ± 8.2 ng/L vs. −3.1 ± 6.5 ng/L; between-group difference in change was −12.3 ng/L (95% CI: −17.8 to −6.8; p < 0.001; adjusted p = 0.005). No significant differences were observed for p-CS, IL-6, or MDA after correction. Conclusions: Synbiotic supplementation over a 10-month period resulted in a trend toward decreased serum IS levels in patients with advanced CKD, suggesting potential benefits of microbiota-targeted therapies. However, no significant effects were observed on renal function, inflammatory, or oxidative stress markers. Further large-scale studies are warranted to confirm these findings and explore the long-term impact of synbiotics in CKD management.